An Evaluation of Internship Programme in Improving Graduate Skills and Marketability Among Arabic Language students in IIUM from the Perspective of Malaysian Job Market - Sahrir, Muhammad Sabri; Ismail, Taufik; Mustapha, Nik Hanan; Abu Bakar, Radhwa; Man, Saupi; Ahmad, Muhammad Anwar; Mokhtar, Maahad (American Research Institute for Policy Development, 2016)
The requirement of employability in the job market initiated universities to conduct internship training as part of study plan. There is a need to train the students with the important knowledge and skills related to the workplace and their gained knowledge. This study attempts to investigate the performance of internship training programme in the Department of Arabic Language and Literature, at International Islamic University Malaysia (IIUM). Methodologically, this study was conducted to congregate the opinions and experience about internship programme among Arabic language and literature students. The participants were purposively selected from 57 students who have completed their three months internship either in the public or private sector from June to September 2015 by using an online survey and open-ended questionnaires. General findings from this study show that internship training has essentially improved their soft skills and increased their work-place literacy and well-being. Despite the poor perception of Arabic language in the mutual graduate employability as well as its practicality aspects and job market by the industry, Arabic language and literature students are well accepted in both private and public sectors to undertake their internship training as reported in this paper. In conclusion, internship training is crucial, particularly among Arabic language and literature students as it enriches their experiences, knowledge and skills both in the personal and social life. It also increased their level of confidence to explore their future opportunity in the Malaysian job market including setting up their own businesses through entrepreneurship knowledge and skill.